Healing a teen's grieving heart : 100 practical ideas - Wolfelt, Alan. (Fort Collins, Colo. : Companion Press, 2001)
This book is for adults who want practical, day-to-day how -to for helping the grieving teens in their lives.
"For families, friends, and caregivers"-- Cover.
Keywords: Bereavement in adolescence -- Problems, exercises, etc; Grief in teenagers -- Problems, exercises, etc; Teenagers and death; Teenagers -- Counseling of; Loss (Psychology) -- Problems, exercises, etc